Refurbish The Rubbish-Land - Fritz Akhmad Nuzir (JURNAL ARSITEKTUR, 2010)
Landfill nowadays is still considered as the cheapest solution in waste management especially for municipalities in developing countries. For these countries, roughly, it only requires an open space in particular location with several precondition, manual collecting mechanism (sometimes involving private partnerships), relatively low cost maintenance (mainly for the collecting instrument e.g.: trucks, containers, etc) and some very brief regulation for the waste management.Â The technical requirements and regulations for a landfill has been developed from time to time and proved it has increased to high level of safety and effectiveness of a landfill operation, but in the end it only causes a high number of operational costs. Even furthermore in European Union level, one directive about Landfill (Council Directive 1999/31/EC of 26 April 1999 on the landfill of waste) has been adapted and amended among the member countries only to result a so called âModern Landfillâ which characterized with strict controls of the potential impacts and sophisticated high cost technology. But this modern landfill still cannot cover the fact that the environmental impacts behind each landfill arent disarmed yet. Therefore recently there are even more and more landfills or ex-landfills are putting under reclamation while as a substitute, some alternatives of waste management have been introduced and proved to be more environmental friendly.Â There are many open landfill sites in Indonesia, which is mainly the general household rubbish, and most of the sites are used without any appropriate treatments and maintenances. Therefore nowadays, there are many concerns, issues, and problems following the existing landfills operation as well. And it will be even much more in the future regarding to the environmental pre-caution.Â The objective of this paper firstly is to initate a way to prepare the transition of waste management in such developing country as Indonesia into non landfill approaches in context of landscape design and planning by creating development scenarios of reuse and reclamation the space within environmental, economical, social and time concern. Secondly, introducing new methods and technologies of municipal waste management as alternatives solutions particularly in sustainable ecologically ways for developing countries would be the inseparable complement of this paper.